(untitled) ("Conference on Universal Science Research 2023", 2025)
This article examines the issues of development and improvement of the hotel industry in Uzbekistan and analyzes the main factors contributing to the development of this sector. The study emphasizes the modernization of hotel infrastructure, improving the quality of service, the introduction of digital technologies, the development of international cooperation and the support of sustainable tourism. Statistics for 2023-2024 show that the number of hotels in Uzbekistan is growing rapidly. The study highlights that the introduction of innovative technologies, the provision of tax incentives and the adoption of eco-tourism strategies contribute to the sustainable development of the hotel industry